Acupuncture for tumor-related depression: a systematic review and meta-analysis - Li, Xiaoyi; Wang, Yang; Wu, Liu; Zhao, Xinyu; Zhu, Tianmin (Frontiers in Oncology, 2023)
Introduction: Tumour-related depression is a series of symptoms or states triggered by tumour as the basic disease. It does not belong to psychiatric depression but dramatically affects individuals' quality of life. Acupuncture is extensively used to treat tumour-related depression, but the effect of body acupuncture on tumour-related depression is still unsubstantiated. This work therefore set out to assess the effect of acupuncture on tumour-related depression.Methods: Eight databases were searched from inception to October 2022 for randomized controlled trials (RCTs). Two researchers separately implemented the database search, study selection, data extraction and quality assessment. All analyses were performed by using Review Manager 5.3.A total of ten studies including 725 participants were included. A majority of studies recruited patients diagnosed with various tumour types and statuses. Meta-analysis revealed that acupuncture had a beneficial effect compared with usual care on Hamilton depression scale (HAMD) (MD = −2.23, 95% CI [−4.43, -0.03], P = 0.05), self-rating depression scale (SDS) (MD= −6.22, 95% CI [-10.67, -1.78], P = 0.006), effective rate (RR = 1.23, 95% CI [1.06, 1.43], P = 0.006) and quality of life questionnaire (QLQ-C30) (MD = 6.08, 95% CI [3.72, 8.43], P＜0.0001). In the dimension of Hamilton depression scale (HAMD) (MD = −4.41, 95% CI [-6.77, -2.05], P = 0.0002) and self-rating depression scale (SDS) (MD = −9.19, 95% CI [-13.14, -5.24], P＜ 0.00001), subgroup analysis also highlighted that acupuncture combined with usual care had an advantage over usual care. But there was no superiority in acupuncture itself compared to usual care about Hamilton depression scale (HAMD) (MD = −1.25, 95% CI [-4.34, -1.84], P = 0.43) and self-rating depression scale (SDS) (MD = −3.08, 95% CI [-11.14, 4.98], P =0.45). Acupuncture also reduced the incidence of adverse effects (RR=0.43, 95% CI [0.23, 0.80], P = 0.008).